1993
DOI: 10.1016/0168-6496(93)90036-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the temperate actinophage φC31 and Streptomyces lividans in soil and the effects of competition and selection on lysogens

Abstract: Lysogenic infections were demonstrated m microcosms of sterde soil Inoculated with Streptomyces hvtdans and the thC31 derwatwe, KC301, in free state or via lysogemzed hosts Intermittent SOil mixing caused liberation of KC301 due to lysis of germinating lysogemzed and uninfected spores The presence of lysogentzed hosts ensured that KC301 was maintained at a constant density The lysogen S hwdans TK24 (KC301) achieved a population density lower than that of tts non-lysogemzed counterpart. Thiostrepton in the sod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The results of Pantastico-Caldas et al [39] suggested that the presence of the virulent Bacillus subtilis phage, SP10C, in soil resulted in a decrease in the host population level by one order of magnitude. The lytic action of the temperate actinophage KC301 appeared to have no numerical impact on streptomycete populations in sterile and nonsterile soil [40][41][42]. Where the infection efficiency of KC301 was sufficiently high to retard vegetative growth of Streptomyces lividans in sterile soil, sporulation compensated for the reduction in propagule numbers (Fig.…”
Section: The Impact Of Phages On Host Populationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of Pantastico-Caldas et al [39] suggested that the presence of the virulent Bacillus subtilis phage, SP10C, in soil resulted in a decrease in the host population level by one order of magnitude. The lytic action of the temperate actinophage KC301 appeared to have no numerical impact on streptomycete populations in sterile and nonsterile soil [40][41][42]. Where the infection efficiency of KC301 was sufficiently high to retard vegetative growth of Streptomyces lividans in sterile soil, sporulation compensated for the reduction in propagule numbers (Fig.…”
Section: The Impact Of Phages On Host Populationsmentioning
confidence: 99%
“…Lysogenic conversion can also confer pathogenicity, for example the prophage of lysogenic Corynebacterium diptheriae strains encodes the toxins enabling establishment of bacterial infection in hosts [7]. Engineered phages containing antibiotic and heavy metal resistance determinants [40,41,[44][45][46] may be advantageous to lysogenic hosts in selective environments [42].…”
Section: The Importance Of Lysogeny In Naturementioning
confidence: 99%
See 3 more Smart Citations